A scoping review on implementation of I-think maps and its effects on higher order thinking skills in Malaysian schools / Lina Mursyidah Hamzah and Wan Mazwati Wan Yusoff - Hamzah, Lina Mursyidah; Wan Yusoff, Wan Mazwati (Universiti Teknologi MARA, 2021)
Malaysian schools have been implementing i-Think program as a means to develop higher order thinking skills among primary and secondary school students since 2013. Thus, there is a need to assess the implementation of the i-Think program since it was made compulsory almost seven years ago. This paper reports a scoping review of research activities conducted on the implementation of the i-Think program in Malaysian schools to synthesize studies on the implementation of the i-Think program in the classrooms; teachers' and students' acceptance of the program; examine its impact on HOTS and students' achievement; and to identify and disseminate the gaps in the works of literature. Forty articles were reviewed and the results indicated that the data on how i-Think programs were implemented in classrooms were so small that no definite conclusions could be made. Results on both students' and teachers' levels of knowledge on i-Think maps were mixed. Majority of studies showed that i-Think maps significantly enhanced students' achievement. However, no study measured the impact of i-Think on HOTS despite researchers' claim that i-Think maps had stimulated students' HOTS. Thus, future studies should focus on showing correlation between i-Think and HOTS by using a validated measurement scale to assess students' HOTS, development of valid and reliable measurement scale to gather a large pool of data to illustrate more comprehensively the status of i-Think implementation in schools throughout Malaysia, support systems provided to teachers at school and district level, and identifying barriers that hinders teachers from implementing i-Think program.